2022
DOI: 10.3390/v14050997
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expression of Selected Interleukins in HIV-Infected Subjects Undergoing Antiretroviral Therapy

Abstract: The use of combined antiretroviral therapy (cART) inhibits the replication of the Human Immunodeficiency Virus (HIV) and thus may affect the functioning of the immune system, e.g., induce changes in the expression of certain cytokines. The aim was to examine the effect of cART on the expression of selected cytokines: interleukin -4, -7 and -15 in HIV-infected subjects. The test material was the plasma of HIV-infected men and healthy men (C, control group). The levels of interleukin were measured by immunoenzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It has been reported that accumulation of ICAM-1, TNF-RII, VCAM-1, and D-dimer in the vessel wall is a hallmark of atherosclerosis and acute coronary syndrome and is mediated by the interaction between adhesion molecules on endothelial and circulating cells ( 28 , 29 ). Proinflammatory cytokine IL-8 ( 30 ) and inductive cytokine IL-7 were elevated ( 31 ) in HIV infection and promote virus replication ( 32 ). The immune-metabolic networks revealed that HIV suppression through ART attenuates the pro-inflammatory status and risk for cardiovascular disease but might contribute to dysregulation of lipid and amino acid metabolisms in the meantime.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that accumulation of ICAM-1, TNF-RII, VCAM-1, and D-dimer in the vessel wall is a hallmark of atherosclerosis and acute coronary syndrome and is mediated by the interaction between adhesion molecules on endothelial and circulating cells ( 28 , 29 ). Proinflammatory cytokine IL-8 ( 30 ) and inductive cytokine IL-7 were elevated ( 31 ) in HIV infection and promote virus replication ( 32 ). The immune-metabolic networks revealed that HIV suppression through ART attenuates the pro-inflammatory status and risk for cardiovascular disease but might contribute to dysregulation of lipid and amino acid metabolisms in the meantime.…”
Section: Discussionmentioning
confidence: 99%